Microchannels Effective Method for the Extraction of Oleuropein Compared with Conventional Methods - Mahnaz Yasemi; Amir Heydarinasab; Masoud Rahimi; Mehdi Ardjmand (Journal of Chemistry)
Different methods of oleuropein extraction from olive leaf were investigated, including maceration, soxhlet, ultrasonic-assisted extraction, and microchannel. In current research, a response surface methodology (RSM) was used for prediction of the optimal values of parameters affecting the extraction of oleuropein through two methods of ultrasound and microchannel. Frequency (F), temperature (T), and power of ultrasound (P) were the parameters which were studied in ultrasound method, but in microchannel system effects of pH and temperature (T), volumetric flow rate ratio of two phases (VR), and contact time (CT) of two phases were optimized. UV detector device at 254 nm was used to recognize oleuropein through comparison of the retention time of the extracts with standard compound in chromatogram. The analysis of extracts was performed using HPLC. Optimum conditions for ultrasound were obtained as follows: F=80 kHz, T = 25°C, and P=100 w. Using these optimum conditions, the extraction of oleuropein was 81.29%. Amount of oleuropein extraction by microchannel method in optimum conditions was 96.29%, which was way more than other applied methods. Microchannel system as a continuous method has many advantages including low solvent consumption, being environment friendly, short time for extraction, and high efficiency.